Cultural Identity of Public Consciousness in Kazakhstan Literature Education: Effects of a New Teaching Method - Kabylov, Adilet; Anes, Garifolla; Kamarova, Nagbdu; Burkitbaeva, Anar; Zhailovov, Baktybay; Shokhayev, Mustafa (Journal of Ethnic and Cultural Studies, 2024)
This study examined the effect of the new teaching method applied in the Kazakh literature course on students' cultural identity and sensitivity, patriotic consciousness, and achievement. In this context, the experimental group experienced innovative teaching methods based on the works of Abish Kekilbayev. This quasi-experimental study examined the effects of educational activities on achievement, social consciousness, citizenship, cultural identity, and sensitivity based on the works of Abish Kekilbayev, a leading Kazakhstania writer, among second-year university students. The experimental group underwent the new teaching method, while the control group followed the activities outlined in the current Kazakh literature textbooks. The effectiveness of the method was assessed through post-test applications. The results indicated significant differences in students’ academic achievement, citizenship, social consciousness, cultural identity, and sensitivity between the experimental and control groups, highlighting the substantial impact of the new method. Similar approaches can be applied to students at various educational levels. Additionally, a comprehensive citizenship and identity education program could be developed by closely examining the works of Abish Kekilbayev and other similar authors in detail.